Wood Connection Techniques In The Main Structure Of Madura Traditional Houses - Dwi Budayana Eka Dewantara; Imam; Erna Winansih (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study briefly introduces the connection techniques used in the main architectural structures of traditional Madurese houses. Traditional Madurese houses, found throughout the island of Madura, East Java, Indonesia, are a rich manifestation of local wisdom, utilizing wood materials and nail-less construction techniques to achieve structural resilience amidst climatic and geographical challenges, including the potential for earthquakes. The primary objective of this study is to identify, describe, and document the types of wood connections in the main structures of traditional Madurese houses, such as the pillars (sasaka) and main beams (soddhu' and brunjung). The research method used is a descriptive qualitative approach, based on field observations, a literature review, and interviews with residents and local traditional carpenters. The study's results are expected to demonstrate that the wood structures of traditional Madurese houses rely heavily on key-jointing and precise interlocking joints, without the use of iron nails or wooden dowels. These joints not only serve as mechanical connections but also help evenly distribute loads and provide semi-rigid flexibility, which is essential for the structure's resistance to lateral forces. For example, the joints on the sasaka (main pillars) are designed to minimize tensile and shear stresses, utilizing the compressive forces and internal friction of the material. In conclusion, the joint techniques in traditional Madurese houses reflect sustainable design principles and a rich traditional knowledge. The reliability of these nail-less joints offers a construction model that is not only environmentally friendly by reducing reliance on industrial materials but also seismically adaptive. This study is expected to contribute to the conservation and revitalization of Madurese architectural heritage and to inspire the development of resilient, sustainable modern wood-construction techniques.